LITERACY DEVELOPMENT THROUGH THE INCORPORATION OF LITERATURE IN LANGUAGE EDUCATION FOR MALAYSIAN SECONDARY SCHOOL STUDENTS - Malachi Edwin Vethamani; Premalatha Nair (Universitas Katolik Indonesia Atma Jaya, 2009)
Literacy is a major concern among educators in the Malaysian education scenario. Various programmes have been identified and implemented in primary and secondary schools to raise the standard of the English language among students. Among them is the implementation of various English language reading programmes. This move has been seen as necessary as part of the Malaysian government’s efforts to make all Malaysians proficient in the English language. To this end, the Malaysian Ministry of Education has incorporated literature into the English language subject. Despite the concerted efforts from the various sections of the Ministry of Educations, the effectiveness of these programmes has been unclear. This study looks into the various programmes implemented in the Malaysian primary and secondary schools. Using a questionnaire, the study attempts to identify students’ perception on the types of literary genre they enjoy reading. The study also looks into the various activities carried out by English teachers and students’ views on the types of activities they enjoy and found useful in the classroom. Keywords: English as a second language, literacy, literature, reading programmes, literary genre.